Ethics of Government Public Communication in Social Media for COVID-19 Management in Makassar City - Siti Nurhazila Febryna Khaidir; Ihyani Malik; Muhammad Randhy Akbar (Mengeja Indonesia Publisher, 2022)
Communication Ethics play a crucial role in shaping public behavior and responses to government efforts in handling the COVID-19 pandemic in Makassar City. This study employs a qualitative descriptive research method, utilizing in-depth interviews with key informants from election organizers in Indonesia and data analysis techniques with NVivo 12 Plus software. The research explores the application of Communication Ethics principles, including the Principles of Beauty, Equality, Kindness, Justice, Freedom, and Truth, in the Instagram account @dpramdhanpomanto's posts related to COVID-19 management in Makassar City. The findings reveal that the Principles of Beauty, Equality, Kindness, Justice, Freedom, and Truth have been applied in the delivery of information regarding COVID-19 handling in Makassar City. However, public understanding and satisfaction with the application of these principles vary. Despite the government's efforts to employ these Communication Ethics principles, some community members remain unsatisfied or do not fully comprehend the principles' application. This study provides valuable insights into the importance of Communication Ethics in government-public interactions during the COVID-19 pandemic. By analyzing the case of the @dpramdhanpomanto Instagram account, the research contributes to a better understanding of how the application of Communication Ethics principles influences public perception and response. The findings offer valuable information for policymakers and practitioners to improve communication strategies and foster public trust and collaboration in addressing the ongoing pandemic.